2021
DOI: 10.1002/cad.20429
|View full text |Cite
|
Sign up to set email alerts
|

The association between moral identity and moral decisions in adolescents

Abstract: The present study explores moral identity, moral emotion attribution, moral responsibility, acceptability, and moral decisions in adolescents. We hypothesized that moral identity predicts moral decisions in adolescents. Furthermore, we hypothesized that moral emotions mediate the relationship between moral identity and moral decisions and moral identity and moral responsibility/acceptability. A total of 749 adolescents were recruited. Questions regarding moral identity, moral emotion attribution, moral respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 52 publications
2
5
0
Order By: Relevance
“…This may provide evidence that a person’s internalized norms influence emotions and are thus indicators of moral identity. The results are consistent with the path analysis of Schipper and Koglin ( 2021b ), in which the heuristic model of Oser ( 2013 ) was empirically tested and moral identity was named as the central point of moral motivation.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This may provide evidence that a person’s internalized norms influence emotions and are thus indicators of moral identity. The results are consistent with the path analysis of Schipper and Koglin ( 2021b ), in which the heuristic model of Oser ( 2013 ) was empirically tested and moral identity was named as the central point of moral motivation.…”
Section: Discussionsupporting
confidence: 88%
“…Given the body of research it could be shown, contrary to the present study results, that high moral identity is negatively related to the attribution of moral emotions and that these predict behavior. This is because the higher the moral identity, the worse adolescents feel about their selfish decisions (Schipper & Koglin, 2021b ; Stets & Carter, 2011 ). The direction also contradicts the theoretical assumptions of Oser ( 2013 ) in which he states that moral action can be derived from moral emotions and moral identity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moral judgement in adolescence is regarded as an important period to develop moral maturity in facing social challenges (Escorza & Ornelas, 2018;Schipper & Koglin, 2021). Particularly for secondary school students, moral judgement serves as a pivotal indicator of their moral development.…”
Section: Introductionmentioning
confidence: 99%